2007
DOI: 10.1186/1477-7827-5-1
|View full text |Cite
|
Sign up to set email alerts
|

The sensitivity of murine spermiogenesis to miglustat is a quantitative trait: a pharmacogenetic study

Abstract: Background: A major event in the post-meiotic development of male germ cells is the formation of the acrosome. This process can be perturbed in C57BL/6 mice by administration of the small molecule miglustat (N-butyldeoxynojirimycin, NB-DNJ). The miglustat-treated mice produce morphologically abnormal spermatozoa that lack acrosomes and are poorly motile. In C57BL/ 6 mice, miglustat can be used to maintain long-term reversible infertility. In contrast, when miglustat was evaluated in normal men, it did not affe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
28
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 31 publications
1
28
0
Order By: Relevance
“…Therefore impairment of spermatogenesis has been observed in mice that have, on the one hand, at least in part a C57BL/6 background, and, on the other hand, diminished GBA2 activity (through disruption of the GBA2 gene or via administration of imino sugars). We have found that NB-DNJ-treated inbred mice with genetic backgrounds unrelated to C57BL/6 have levels of testicular GlcCer as high as in C57BL/6 mice, but without a reproductive phenotype (23). We have also seen that NB-DNJ elevates GlcCer in FVB/N x C57BL/6 hybrid mice, whereas only in a minority of these hybrids is spermatogenesis affected (23).…”
Section: Discussionmentioning
confidence: 69%
See 4 more Smart Citations
“…Therefore impairment of spermatogenesis has been observed in mice that have, on the one hand, at least in part a C57BL/6 background, and, on the other hand, diminished GBA2 activity (through disruption of the GBA2 gene or via administration of imino sugars). We have found that NB-DNJ-treated inbred mice with genetic backgrounds unrelated to C57BL/6 have levels of testicular GlcCer as high as in C57BL/6 mice, but without a reproductive phenotype (23). We have also seen that NB-DNJ elevates GlcCer in FVB/N x C57BL/6 hybrid mice, whereas only in a minority of these hybrids is spermatogenesis affected (23).…”
Section: Discussionmentioning
confidence: 69%
“…We have found that NB-DNJ-treated inbred mice with genetic backgrounds unrelated to C57BL/6 have levels of testicular GlcCer as high as in C57BL/6 mice, but without a reproductive phenotype (23). We have also seen that NB-DNJ elevates GlcCer in FVB/N x C57BL/6 hybrid mice, whereas only in a minority of these hybrids is spermatogenesis affected (23). Thus the consequence of GBA2 deficiency and GBA2 inhibition through lowdose imino sugar treatment seems universal (higher level GlcCer), but the impact of this alteration on male germ cell development is dependent on genetic background.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations